Gunshot casualties in Israel: A decade of violence. Issue 10 (October 2022) - Goldman, Sharon; Bodas, Moran; Lin, Shaul; Radomislensky, Irina; Levin, Liran; Bahouth, Hany; ,; Acker, A.; Bahouth, H.; Bar, A.; Becker, A.; Braslavsky, A.; et al.
Highlights: The number of gunshot wound related hospitalizations in Israel more than doubled over the past decade. Gunshot related hospitalization were disproportionally more prevalent among Arab males, fivefold more than Jewish males. No significant differences between Jews and Arabs were reported regarding in-hospital mortality. The findings should alert policymakers of this urgent problem, and the immediate necessity in implementing focused interventions. Abstract: Objective: The purpose of this study was to identify and characterize casualties hospitalized with assault (non-terror) related gunshot wounds (GSW) in Israel as a basis for determining the incidence, trends and at-risk population groups. Methods: This retrospective cohort study is based on data from the Israel National Trauma Registry. The data includes GSW casualties hospitalized between January 1, 2011 and December 31, 2020. Attempted suicide, unintentional injury, legal intervention, children (ages 0–9) and terror (Israeli-Arab conflict) related GSW were excluded. The remaining population was classified with an ICD-9-CM diagnosis code of 965.0–965.4. Results: The study population included 2, 763 GSW admissions. A noticeable increase in GSW casualties was reported, from 206 hospitalization in 2011 to 456 in 2020. The proportion of Arab casualties increased from 73.3% of all GSW casualties in 2011 to 90.8% in 2020, far more than their proportion in the population (∼20%). The majority of the GSW casualties were males (95.8%) and between the ages of 20 and 29 (42.2%). Among severe/critical casualties, 19% of Arabs and 9.9% of Jews arrived by private car. Severe thoracic and abdominal injuries were the prominent injuries among fatal casualties (47.6 and 40.8, respectively). While the all-severity mortality rate was 5.6% ( n = 147), 24.4% ( n = 135) of severe/critical (ISS16+) casualties died, with no significant differences between Jews and Arabs. Forty percent of deaths occurred in the emergency department. Conclusions: This study establishes that during the past decade in Israel, not only has there been a continuous increase in hospitalizations due to GSW, but also Arabs are at great risk of such related hospitalizations. Preventive strategies targeting at-risk groups are crucial for minimizing morbidity and mortality related to GSW in Israel.